INTEGRASI NILAI-NILAI KURIKULUM BERBASIS CINTA DALAM PEMBELAJARAN DAN BUDAYA MADRASAH MEWUJUDKAN PENDIDIKAN RAHMATAN LIL 'ALAMIN - Rendy .S. Sambara; Gesika Avelina; Ramadan; Sanrina Laknasa (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
The Love-Based Curriculum represents a new paradigm in Islamic education that places compassion as the fundamental principle of teaching and school culture. This study aims to analyze the integration of Love-Based Curriculum values into classroom learning and madrasah culture and examine its contribution to the realization of Rahmatan lil 'Alamin education. This study employed a qualitative approach using a literature review method. Data were collected from scholarly journal articles, books, and policy documents published between 2021 and 2026 and analyzed through content analysis. The findings indicate that the implementation of the Love-Based Curriculum can be achieved by integrating values of compassion, empathy, tolerance, responsibility, and respect for human dignity into learning activities and madrasah culture. Humanistic learning, positive school culture, teachers' role modeling, and religious habituation are key factors in developing students who are moderate, inclusive, and possess noble character. Therefore, integrating the Love-Based Curriculum contributes to establishing Rahmatan lil 'Alamin education that fosters knowledgeable, faithful, and morally responsible individuals.